2006
DOI: 10.1007/s00268-005-0490-2
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of the Gastrointestinal Tract Secondary to Ingestion of Foreign Bodies

Abstract: Ingested FB perforation in the adult population is most commonly secondary to unconscious accidental ingestion and is frequently caused by dietary FBs especially fish bones. A preoperative history of FB ingestion is thus rarely obtained, although wearing dentures is a common risk factor. FB perforations of the stomach, duodenum, and large intestine tend to present with a longer, more innocuous clinical picture than perforations in the jejunum or ileum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
372
0
29

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(404 citation statements)
references
References 23 publications
3
372
0
29
Order By: Relevance
“…The most common types of FB in adults were fish bones and meat. 5,12,13 The clinical symptoms of IFB varied according to the location of the FB in the patient's body. When FB were located near the pharyngolarynx, the patients usually complained of a feeling of irritation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common types of FB in adults were fish bones and meat. 5,12,13 The clinical symptoms of IFB varied according to the location of the FB in the patient's body. When FB were located near the pharyngolarynx, the patients usually complained of a feeling of irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency surgery within the appropriate time cannot be avoided in these cases. 5 The treatment method for IFB depends on each case and requires consideration of the characteristics, shapes, and location of the FB within the GI tract or abdomen, as well as patients' medical histories and physical examinations. There is no definitive protocol to deal with IFB.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, free sub-diaphragmatic air is not frequently observed in GIS perforations (1). Goh et al (2) specified that free air under the diaphragm was present in only 15.9% of the cases. The reason behind this can be explained as follows: once the foreign material perforates the intestinal wall, the consequent inflammatory mass is covered by granulation tissue, intestinal wall, omentum and fibrin (7).…”
Section: Discussionmentioning
confidence: 99%
“…Perforation most often occurs in the terminal ileum and recto-sigmoid region, which anatomically show angulation (1, 2). Goh et al (2) reported that intra-abdominal perforations most frequently influence the terminal ileum, with a rate of 38.6%. Terminal ileum perforations are not initially considered as part of differential diagnosis since they clinically mimic acute appendicitis and diverticulitis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Such deliberate ingestions of foreign bodies are rare in conscious and healthy people but are frequently seen in psychiatric, insane and retarded adults. (4) Most of the intentional and repeated swallowing has a psychiatric background which had not been given much attention in the past. (5) There may be an element of seeking attention or escaping responsibilities in such subjects but most of the studies have suggested that the subjects are usually mentally retarded and have significantly low IQ.…”
Section: Introductionmentioning
confidence: 99%